Making the Private Public: A Delivery of Palestinian oil in third/ninth-century Egypt - Sijpesteijn, Petra Marieke (Studia Orientalia Electronica, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-GB; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-GB">A short document written on papyrus records an order for the delivery of Palestinian oil in third/ninth-century CE Egypt. It reveals interesting information concerning transregional trade relations, commercial infrastructures and the logistics of product distribution, as well as document-validation practices and the legal status and authority of documents, especially those of a semi-public nature. The text will be compared to similar orders of payment and delivery, and read for evidence of local patterns of patronage and systems of care in mediaeval Egypt.